Figure 3 from: Juswara L, Schuiteman A, Droissart V (2016) Four new orchid species from the Lengguru fold belt, West Papua, Indonesia. PhytoKeys 61: 47-59. https://doi.org/10.3897/phytokeys.61.7590 - Juswara, Lina; Schuiteman, Andre; Droissart, Vincent (Zenodo, 2016)
Figure 3 - Photographs of living type specimens and habitats. Bulbophyllum leucoglossum: A habitat and habit B flower, side view C flower, front view D Flower close-up, showing details of the column and the labellum. Dendrobium centrosepalum: E habitat and habit F, G plant and inflorescence H inflorescence and flowers close-up. Photos: Vincent Droissart.